2009
DOI: 10.1016/j.neurobiolaging.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-1 mutation impairs cholinergic modulation of synaptic plasticity and suppresses NMDA currents in hippocampus slices

Abstract: Presenilin-1 (PS1) mutations cause many cases of early-onset inherited Alzheimer's disease, in part, by increasing the production of neurotoxic forms of amyloid β-peptide (A β). However, Aβ -independent effects of mutant PS1 on neuronal Ca 2+ homeostasis and sensitivity to excitatory neurotransmitters have been reported. Here we show that cholinergic modulation of hippocampal synaptic plasticity is impaired in PS1 mutant knockin (PS1KI) mice. Whereas activation of muscarinic receptors enhances LTP at CA1 synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 51 publications
8
47
0
Order By: Relevance
“…These results suggest that increased ER Ca 2þ release in PS1 knock-in mice results in (a compensatory) inactivation=desensitization of NMDA receptors. Similar results were found in neurons of so-called triple transgenic mice (that in addition to the PS1 mutant knock-in express APP and tau protein mutations) (92). Interestingly, Ab also has been found to inhibit glutamatergic synaptic transmission (through NMDA receptor stimulation and possibly desensitization).…”
Section: Ca 2þ Homeostasis and The Ersupporting
confidence: 70%
See 1 more Smart Citation
“…These results suggest that increased ER Ca 2þ release in PS1 knock-in mice results in (a compensatory) inactivation=desensitization of NMDA receptors. Similar results were found in neurons of so-called triple transgenic mice (that in addition to the PS1 mutant knock-in express APP and tau protein mutations) (92). Interestingly, Ab also has been found to inhibit glutamatergic synaptic transmission (through NMDA receptor stimulation and possibly desensitization).…”
Section: Ca 2þ Homeostasis and The Ersupporting
confidence: 70%
“…For example, it was found that in mutant PS1 knock-in mice LTP was not impaired, but the effect of cholinergic transmission was reversed (i.e., instead of enhancing LTP, cholinesterase inhibitors caused LTP reduction in these mice). It was found that NMDA receptor currents in these mice were reduced but could be restored to normal levels by intraneuronal Ca 2þ chelation (92). These results suggest that increased ER Ca 2þ release in PS1 knock-in mice results in (a compensatory) inactivation=desensitization of NMDA receptors.…”
Section: Ca 2þ Homeostasis and The Ermentioning
confidence: 84%
“…Facilitated LTP in mutPS1 mice at 4 -5 months of age seems to be a consistent finding in mice overexpressing mutant PS1, but also in PS1 M146V knock-in mice without overexpression (Wang et al, 2009) suggesting that the mutation itself facilitates LTP. Recently, Puzzo et al (2008) strongly supported a model for A␤ effects in which low concentrations play a novel positive, modulatory role on LTP, whereas high concentrations play the wellknown detrimental effect (Jacobsen et al, 2006;Lacor et al, 2007;Shankar et al, 2007;Venkitaramani et al, 2007).…”
Section: Effects Of L286v Ps1 Mutation: a Transient Increase In Synapsupporting
confidence: 56%
“…Priller et al (2007) showed that cultured hippocampal neurons expressing a mutant PS1 exhibited an inhibition of evoked excitatory synaptic currents while the same mutation induces an increased LTP (Dewachter et al, 2008). Likewise, Wang et al (2009) reported that PS1 mutant knock-in mice showed an increased LTP which coincides with decreased NMDA currents at the same age.…”
Section: Effects Of L286v Ps1 Mutation: a Transient Increase In Synapmentioning
confidence: 98%
“…The cholinergic loss is an early marker of memory deficits in Alzheimer's disease, and PS1 mutant knock-in mice show impairment of cholinergic modulation in hippocampal plasticity, providing evidence of cholinesterase inhibitor therapy in dementia. However, the ability of these drugs to lower the epileptic threshold should suggest caution in their use in EOAD [7] .…”
Section: Discussionmentioning
confidence: 99%